A polyaniline/shark skin composite and its conductivity based on polaron hopping. Issue 8 (24th May 2021) - Komaba, Kyoka; Goto, Hiromasa
ABSTRACT: In this study, banded houndshark (triakis scyllium) skin was used for the preparation of a polyaniline (PANI)/shark skin composite. Infrared absorption (IR) and electron spin resonance (ESR) spectroscopy were performed to confirm the surface-layer PANI component. This method of polymerization could help develop the use of natural biological materials for the preparation of functional plastics. The ESR measurements and electrical conductivity of the composite revealed the occurrence of three-dimensional variable range hopping with polarons as charge carriers, leading to Pauli paramagnetism. GRAPHICAL ABSTRACT: